Appropriate technology catalogue - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Tool, the coordination centre for Dutch AT groups, recently published a catalogue of 400 titles focussing mainly on agriculture, food production and rural development. This edition is a selection of the best literature available, selected from...